Do Early Results of Proximal Humeral Allograft-Prosthetic Composite Reconstructions Persist at 5-year Followup?. Issue 4 (April 2019) - El Beaino, Marc; Liu, Jiayong; Lewis, Valerae O.; Lin, Patrick P.
Abstract: Background: Insufficiency of the rotator cuff is a major problem after resections of proximal humeral tumors and can limit shoulder motion despite preservation of the deltoid muscle and axillary nerve. Allograft-prosthetic composite reconstruction offers one method to reattach the rotator cuff tendons and has been successful in small studies with short followup. However, data are lacking with regard to implant durability, changes in Musculoskeletal Tumor Society (MSTS) scores over time, and delayed complications with extended followup. Questions/purposes: (1) What is the cumulative incidence of allograft-prosthetic composite revision surgery 5 years after the procedure? (2) What are the early- and intermediate-term MSTS scores of allograft-prosthetic composite reconstruction of the shoulder? (3) What are the complications of allograft-prosthetic composite reconstruction? Methods: Twenty-one patients underwent allograft-prosthetic composite reconstruction after tumor resection of the proximal humerus between 2000 and 2015. Six patients who were lost to followup were not included. All patients had malignant or aggressive benign tumors that could be treated with a wide intraarticular approach preserving the deltoid muscle, axillary nerve, and glenoid. Cumulative incidence of implant revision was calculated with death of the patient as a competing risk. Minimum followup was 24 months (with the exception of one patient who died at 22 months), and median followup was 97 months (range, 20-198 months). The upper extremity MSTS score was used to assess function. Various complications were identified from radiographs and charts. Results: The cumulative risk of implant revision was 10.1% at 5 years (95% confidence interval [CI], 1.6%-28.0%). Mean MSTS scores were 86% (± SD 9%) at 1 year and 78% (± SD 13%) at 5 years (mean difference ± SD 9% ± 14%, p = 0.015). Mean active forward elevation was 101° (± SD 33°) at 1 year and 92° (± SD 34°) at 5 years (mean difference ± SD 8° ± 36°, p = 0.41). Notable adverse events included progressive radiographic superior subluxation > 1 cm after 12 months followup (12 of 21 patients), delayed union > 12 months (10 of 21 patients), resorption of the greater tuberosity (nine of 21 patients), and aseptic loosening (three of 21 patients). Conclusions: At intermediate 5-year followup, allograft-prosthetic composite reconstruction of the proximal humerus has an acceptable overall MSTS score and a low incidence of implant revision, but loss of patients to followup and exclusion from the study likely make the results seem better than they actually are. The MSTS score deteriorates between 1 and 5 years. Decreased active forward elevation is not likely to be the sole reason for worsening MSTS scores. A variety of delayed complications including delayed union, resorption of the greater tuberosity, and superior subluxation occurs frequently and may contribute to overall scores. Future studies that compare allograft-prosthetic composites against other forms of reconstruction should attempt to control for possible selection bias and have sufficiently long followup to detect the deterioration of MSTS scores that occur with time. Level of Evidence: Level IV, therapeutic study.